Digital Readiness Amidst Rural Realities: A Phenomenological Inquiry into Papuan Pre-service Teachers’ Experiences - Dewi Zulaiha (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The digital transformation of Indonesian education faces severe geographical and infrastructural hurdles, particularly within the Papua region, where a persistent digital divide complicates the implementation of modern educational standards. This phenomenological study explores how 26 Papuan pre-service teachers navigate the demands of the digital age alongside the mandates of the Kurikulum Merdeka (Independent Curriculum). Utilizing a qualitative approach, the research analyzes data collected from students across various districts in Biak to reveal the lived experiences of future educators in underdeveloped areas. The findings highlight a sharp contrast between professional idealism and structural reality; while these pre-service teachers demonstrate high levels of resilience by prioritizing